An assessment of the functioning of the municipal offices of Świętokrzyskie province - Kusto, Barbara (Ocena funkcjonowania urzędów gmin miejskich w województwie świętokrzyskim, 2019)
In this study, the issue of the efficiency of functioning of local government institutions was taken up. The efficient operation of a local government administration office has a significant impact on the development of the local community and satisfying the needs of its residents. The aim of this article is to measure and assess the potential institutional efficiency of municipal offices in the Świętokrzyskie province [voivodeship]. The article uses the institutional analysis method. The research results indicate that the municipalities of the Świętokrzyskie province are characterized by low institutional efficiency, especially in such areas as the provision of public services and the management of human resources. The most favorable situation occurred in the areas of strategic and financial management as well as in social participation and the stimulation of social development
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 152-162
Keywords: local government administration; institutional analysis; institutional efficiency; commune; municipal office; administracja samorządowa; analiza instytucjonalna; sprawność instytucjonalna; urząd gminy